State property rights protection outside the territory of the Russian Federation - Aleksandrovich Vlasov, Anatoly; Nikolaevich Levushkin, Anatoly; Leisan Emilevna Rakhmatullina, Takhir Emilevich Rakhmatullin, (Opción, 2019)
The paper deals with the protection and immunity of the Russian property, including the diplomatic one, outside the territory of the Russian Federation via comparative qualitative research methods. As a result, the constitutions of individual states, in addition to the value guarantee of protection of the right to property, also fix a judicial guarantee. In conclusion, the legislator needs to develop effective measures to implement various options in the system of the protective mechanism for protecting state property, including diplomatic, outside the Russian Federation.